Lateral force resisting systems in lightweight steel frames: Recent research advances. (September 2018) - Sharafi, Pezhman; Mortazavi, Mina; Usefi, Nima; Kildashti, Kamyar; Ronagh, Hamid; Samali, Bijan
Abstract: Lightweight Steel Frames (LSF) made by framing thin gauge cold-formed steel (CFS) into different structural elements such as walls, trusses and joists are commonplace in Australia and many parts of the world. The great progress in the knowledge of CFS structures achieved in the past two decades, together with the modern design and fabrication methods supported by progressively improved specifications, have equipped the industry of the lightweight steel construction with tools and confidence to play an important part in the future of building construction. Despite the ever-increasing demand on the use of cold formed steel (CFS) framing into more complex and taller structures, the lateral load resistance capacity of lightweight steel frames has proven to be a major hindrance and a major concern. This paper reviews and summarises the research developments made in the area of lateral load resistance capacity of lightweight steel frames (LSF) as published in leading journals and codes' provisions in the area. Research advances in conventional systems such as shear walls clad with face sheathings and LSF strap-braced wall systems in addition to other less conventional systems such as special bolted moment frames are reviewed here, and the solutions for improving the lateral performance of these systems are classified. Highlights: Summarising research developments in lateral load resistance of light steel frames. Shear walls with face sheathings, strap-brace and mixed systems are studied. Solutions for improving the lateral performance of these systems are classified.